Seawater-Mediated Solar-to-Sodium Conversion by Bismuth Vanadate Photoanode- Photovoltaic Tandem Cell: Solar Rechargeable Seawater Battery - Kim, Jin Hyun; Hwang, Soo Min; Hwang, Inchan; Han, Jinhyup; Kim, Jeong Hun; Jo, Yim Hyun; Seo, Kwanyong; Kim, Youngsik; Lee, Jae Sung (iScience, 2019)
Conversion of sunlight to chemical energy based on photoelectrochemical (PEC) processes has been considered as a promising strategy for solar energy harvesting. Here, we propose a novel platform that converts solar energy into sodium (Na) as a solid-state solar fuel via the PEC oxidation of natural seawater, for which a Na ion-selective ceramic membrane is employed together with photoelectrode (PE)-photovoltaic (PV) tandem cell. Using an elaborately modified bismuth vanadate-based PE in tandem with crystalline silicon PV, we demonstrate unassisted solar-to-Na conversion (equivalent to solar charge of seawater battery) with an unprecedentedly high efficiency of 8% (expected operating point under 1 sun) and measured operation efficiency of 5.7% (0.2 sun) and long-term stability, suggesting a new benchmark for low-cost, efficient, and scalable solid solar fuel production. The sodium turns easily into electricity on demand making the device a nature-friendly, monolithic solar rechargeable seawater battery. [Display omitted] •Solar rechargeable battery using natural seawater as a medium was realized•Solar charge was achieved by metal oxide-based photoelectrodes, especially BiVO4•BiVO4-c-Si tandem cell achieved unbiased charge with a high efficiency up to 8% Electrochemical Energy Conversion; Energy Storage; Materials Characterization